Determinants of Tax Avoidance from a Financial Perspective - Nursiam; Kusumawati , Eny (Riset Akuntansi dan Keuangan Indonesia, 2025)
Tax avoidance refers to efforts by taxpayers to reduce tax liabilities by exploiting loopholes in tax regulations. This practice is legal and does not conflict with existing rules. This study aims to analyze financial determinants of tax avoidance, including liquidity, profitability, thin capital, capital intensity, earning power, sales growth, and company size. The research population consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX-IC classification) during 2019–2021. Secondary data were obtained from 159 manufacturing company annual reports available on [www.idx.co.id] (http://www.idx.co.id) and company websites, with purposive sampling used for selection. The study applies a quantitative approach with multiple linear regression analysis. The findings show that tax evasion is negatively impacted by equity-based profitability, suggesting that companies with higher equity returns are less likely to evade taxes. However, firms with larger assets, faster development, and larger scale are more likely to employ tax avoidance tactics, according to the beneficial effects of asset-based profitability, capital intensity, sales growth, and company size. However, thin capitalization has no discernible impact. These results demonstrate that tax evasion is a strategic decision influenced by asset structure, financial situation, and the need for legitimacy, and that it goes beyond simple taxation issues.